Modifikasi Alat Pembelajaran Tolak Peluru Untuk Meningkatkan Hasil Belajar Pendidikan Jasmani Di SDN Sidodadi 04 - Sajiwo, Galih Andre Bagus; Apriliyanto, Rizki; Sulaiman, Ahmad (Universitas Hamzanwadi, 2025)
The purpose of this study was to improve the learning outcomes of grade VI students of SDN Sidodadi 04 through the use of modified tools tennis balls in learning to throw bullets sideways. The problem in this research is the lack of learning tools, especially bullet shot tools, which makes the learning process at SDN Sidodadi 04 less effective. Besides that, many students have difficulty understanding and performing the basic movements of the bullet sideways style, so that their participation and learning outcomes are low. The method used is Classroom Action Research (PTK) in two cycles. The population of this study was class VI students of SDN Sidodadi 04, totalling 15 students. The results of the study showed that in cycle I, as many as 10 students (66.6%) had achieved learning completeness, while 5 students (33.3%) were not yet complete out of a total of 15 students. In cycle II, there was a positive increase, where 13 students (86.7%) achieved learning completeness, while 2 students (13.3%) were still not complete. there was an increase in student learning completeness from 66.6% in cycle I to 86.6% in cycle II. This shows that the modification of learning tools can help students better understand the material and improve their learning results. In conclusion, the application of modified learning tools in the form of tennis balls in bullet throwing activities has proven effective in improving student learning outcomes.